IMPLEMENTASI MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VII-6 DI SMP NEGERI 17 BANDA ACEH - Mastura, Cut Yenni; Desfandi, Mirza; Purnomowati, Dyah Rahmani (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2024)
Critical thinking skills are essential in 21st-century learning and need to be developed in school environments. These skills are crucial for students to analyze information in depth, solve problems effectively, and make appropriate decisions. One effective learning strategy for enhancing critical thinking skills is the Problem-Based Learning (PBL) model. This model emphasizes problem-based learning that requires students to actively discover and develop solutions. This study aims to analyze the implementation of the PBL model in improving the critical thinking skills of seventh-grade students (class VII-6) at SMP Negeri 17 Banda Aceh. This research employs a classroom action research (CAR) method conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The research instruments include critical thinking tests, observation sheets, and interviews with students and teachers. The results indicate that the application of the PBL model significantly enhances students' critical thinking skills. Students become more active in identifying problems, analyzing information, and formulating logical and systematic solutions. Additionally, they exhibit greater independence, confidence, and the ability to collaborate in groups. Student responses to the implementation of the PBL model in learning were highly positive, with a response rate of 90.7%. These findings demonstrate that the PBL model is an effective method for improving students' critical thinking skills. Therefore, teachers are encouraged to implement the PBL model as part of their teaching strategies to enhance student engagement and foster critical thinking skills in the learning process.